Nazarov reagent: a novel reagent for the synthesis of natural products - Kaur, Tanpreet (Synlett, 2006)

Efficient one-pot synthesis of alpha-amino phosphonates catalyzed by bismuth nitrate pentahydrate - Bhattacharya, Asish K.; Kaur, Tanpreet (Synlett, 2007)
A simple, efficient, and environmentally benign method has been developed for the synthesis of alpha-amino phosphonates through a one-pot reaction of aldehydes with amines and diethyl phosphite in the presence of bismuth nitrate pentahydrate as a catalyst. Some of the major advantages of this protocol are: good yields, the involvement of a less-expensive and non-toxic catalyst, mild and solvent-free reaction conditions and also tolerance towards other functional groups present in the substrates. Eighteen examples are described, highlighting the substrate scope of the reaction.
Keywords: aldehydes; alkyl phosphite; alpha-amino phosphonates; amines; bismuth nitrate pentahydrate; synthetic methods

Synthesis of the antibacterial benzoquinone primin and its water-soluble analogue, primin acid - Bhattacharya, Asish K.; Kaur, Tanpreet; Ganesh, Krishna N. (Synthesis-Stuttgart, 2010)
The biologically active natural product, primin and its water-soluble acid analogue, primin acid are prepared in 34% and 25% overall yields, respectively, from a common intermediate using a Grignard reaction and a Johnson-Claisen rearrangement as the key steps.
Keywords: 1; 4-benzoquinones; Antibacterial; Johnson-Claisen rearrangement; primin; primin acid